Effectiveness of Zinc and Gypsum Application Against Cadmium Toxicity and Accumulation in Wheat (Triticum aestivum L.). Issue 14 (6th August 2017) - Abbas, M. S.; Akmal, M.; Ullah, Saif; Hassan, M. U.; Farooq, S.
ABSTRACT: Cadmium (Cd) is a nonessential and toxic element because it inhibits the growth and development of plants and is dangerous for end consumer. It enters in the human food chain through food crops. Application of plant nutrients such as zinc (Zn) and gypsum is a viable and cheap strategy to minimize its accumulation in edible plant portions. Therefore, this investigation was conducted to determine the effectiveness of Zn and gypsum against Cd accumulation in wheat. The results showed that Cd toxicity considerably decreased the plant growth, physiological activities, and yield attributes and increased the Cd accumulation in root, shoot, and grain, while application of Zn and gypsum remarkably increased the growth and yield and decreased the Cd accumulation in plant parts in Cd-contaminated soil. The results also depicted that application of Zn showed better results as compared to gypsum. In conclusion, we can say that application of Zn and gypsum remarkably ameliorated the Cd toxicity and decreased its accumulation in wheat, grown in Cd-contaminated soil.